ANALISIS DAMPAK PANDEMI COVID 19 TERHADAP PERGERAKAN JUMLAH PENUMPANG DI BANDAR UDARA INTERNASIONAL EL TARI KUPANG - Yohanes Don Bosco; Ika Fathin Resti Martanti (Jurnal Publikasi Ekonomi dan Akuntansi, 2023)
Recently, china or what we know as the bamboo curtain country was shocked by the news that one of its 55-years-old citizens from Wuhan, Hubei Province, was infected with a new deadly virus on November 17, 2019. which then spread as a worldwide pandemic. A new type of coronavirus known as SARS-CoV-2 is the cause of this pandemic. In Indonesia, the first case of this virus was found in March 2020. This virus in Indonesia causes an increasing number of deaths, the government’s efforts to accelerate the handling of COVID-19, especially for the aviation sector, by published the circular of the Task Force for the Acceleration of Handling Covid-19 Number 4 of 2020 which limits the travel of people to or from an area in order to accelerate the handling of the spread of the Covid-19 virus. This is one of the triggers for the decreased in the number of passengers at Kupang El Tari International Airport. This type of research is a mixed type of research with a comparative descriptive method, which is to compare the period before and during the Covid-19 Pandemic. In this study, the author only wants to explain the existing data. The method used in this study is a mixed method because the variables studied used data in the form of numbers and verbal data obtained from interviews, observations and documentation. The results of this study can be concluded that the number of passengers in 2019 and 2020 is different.The number of departing passengers at Kupang El Tari International Airport in 2020 are fluctuated. Sometimes up and sometimes down. So, the decrease in the number of passengers from 2019 - 2020 was 44% or 358,324 passengers. So the decrease is significant.